Biodegradation of profenofos, an acetylcholine esterase inhibitor by a psychrotolerant strain Rahnella sp. PFF2 and degradation pathway analysis. (March 2021) - Verma, Shalini; Chatterjee, Subhankar
Abstract: Profenofos (PFF) is an organophosphate insecticide and used worldwide to control harmful pests and insect populations. Removal of PFF from the environment is important because of its high mammalian acute toxicity due to acetylcholinesterase enzyme inhibition. Biodegradation in this context is beneficial as it is a cost-effective and sustainable process. In the present study, microbial degradation of PFF was investigated by using a psychrotolerant bacterium Rahnella sp. PFF2. The bacterial strain was isolated from the soil samples of apple orchards situated in Kufri, Himachal Pradesh, India. Quantitative analysis through High-performance liquid chromatography revealed that the bacterium PFF2 was able to degrade 100% PFF (50 μg/ml) within 14 days at 20 °C, within 16 days at 28 °C, and within 20 days at 15 °C. GC/MS and HPLC studies showed the presence of pathway metabolites 4-Bromo-2-chlorophenol, phosphoric acid, and 3, 4 – dimethyl benzoic acid. Based on these data a probable PFF degradation pathway has been proposed. An inducible and intracellular organophosphorus hydrolase enzyme might responsible for the initial degradation process. To the best of our knowledge, the current finding is the first report of PFF degradation at both the psychrophilic and mesophilic temperature conditions by any psychrotolerant Rahnella sp. isolated from Western Himalayan regions. Graphical abstract: Image 1 Highlights: A psychrotolerant Rahnella sp. was isolated from the apple orchard of HP, India. The strain was efficiently degraded 50µg/ml profenofos at 20 °C, at 28 °C and at 15 °C. 4-Bromo-2-chlorophenol was detected as one of the major pathway metabolites. A probable profenofos biodegradation pathway has been proposed. Enzyme organophosphorus hydrolase might be responsible for initial degradation.